Towards a Rights-Sensitive East African Community - Majamba, Hamudi (Fountain Publishers, Kampala., 2011)
Ethnicity is, a key component of both politics and society because it is the easiest force around which to mobilise. Ethnicity is a phenomenon that has lived with us since time immemorial, yet inadequate attention has been given to address its impact on human rights, governance, social disparities and civil strife.